Shaping the Future of Learning: Strategies, Innovations, and Collaborations at SMA 1 Batik Surakarta Post-Covid-19 - Suranto, Suranto; Mustofa, Rochman Hadi; Yustina, Laily Nur (Buletin Literasi Budaya Sekolah, 2023)
The purpose of this research is to explore the challenges and strategies in implementing post-Covid-19 learning. This study utilizes a qualitative approach with a case study design. Data collection techniques involve interviews, documentation, and observation of learning activities. The informants involved in this research include subject teachers, school principals, vice principals in charge of student affairs, vice principals in charge of the curriculum, and students. In this study, the Miles and Huberman analysis technique is applied, covering data collection, reduction, presentation, and verification. The research results indicate that schools employ various strategies to address learning loss due to the Covid-19 pandemic. These strategies include individualized learning tailored to the needs of students, enhancing project-based learning, and organizing various forms of training for teachers to improve their pedagogical skills. The presence of the Kurikulum Merdeka has also proven to be a supportive aspect in overcoming post-pandemic learning challenges.